Systematic chemical and molecular profiling of MLL-rearranged infant acute lymphoblastic leukemia reveals efficacy of romidepsin - Cruickshank, M.; Ford, J.; Cheung, Laurence; Heng, J.; Singh, S.; Wells, J.; Failes, T.; Arndt, G.; Smithers, N.; Prinjha, R.; Anderson, D.; Carter, K.; et al. (2017)
To address the poor prognosis of mixed lineage leukemia (MLL)-rearranged infant acute lymphoblastic leukemia (iALL), we generated a panel of cell lines from primary patient samples and investigated cytotoxic responses to contemporary and novel Food and Drug Administration-approved chemotherapeutics. To characterize representation of primary disease within cell lines, molecular features were compared using RNA-sequencing and cytogenetics. High-throughput screening revealed variable efficacy of currently used drugs, however identified consistent efficacy of three novel drug classes: proteasome inhibitors, histone deacetylase inhibitors and cyclin-dependent kinase inhibitors. Gene expression of drug targets was highly reproducible comparing iALL cell lines to matched primary specimens. Histone deacetylase inhibitors, including romidepsin (ROM), enhanced the activity of a key component of iALL therapy, cytarabine (ARAC) in vitro and combined administration of ROM and ARAC to xenografted mice further reduced leukemia burden. Molecular studies showed that ROM reduces expression of cytidine deaminase, an enzyme involved in ARAC deactivation, and enhances the DNA damage-response to ARAC. In conclusion, we present a valuable resource for drug discovery, including the first systematic analysis of transcriptome reproducibility in vitro, and have identified ROM as a promising therapeutic for MLL-rearranged iALL.